2018
DOI: 10.1287/mnsc.2017.2902
|View full text |Cite
|
Sign up to set email alerts
|

Advertising Content and Consumer Engagement on Social Media: Evidence from Facebook

Abstract: We describe the effect of social media advertising content on customer engagement using data from Facebook. We content-code 106,316 Facebook messages across 782 companies, using a combination of Amazon Mechanical Turk and natural language processing algorithms. We use this data set to study the association of various kinds of social media marketing content with user engagement-defined as Likes, comments, shares, and click-throughs-with the messages. We find that inclusion of widely used content related to bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
225
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(281 citation statements)
references
References 61 publications
7
225
0
12
Order By: Relevance
“…Engagement, for the purposes of this study, involves interaction with posts on social media and the level of participation in the post (see Oh et al, 2018). These metrics ('likes', 'comments', 're-tweets' and 'follows') are commonly used by industry and are said to be more granular than number of followers (Lee, Hosanagar, & Nair, 2018). The metrics are also measurable actions that consumers take on social media and emphasise the co-creative nature of the medium (Barger et al, 2016;Tafesse, 2016).…”
Section: Consumer Engagementmentioning
confidence: 99%
“…Engagement, for the purposes of this study, involves interaction with posts on social media and the level of participation in the post (see Oh et al, 2018). These metrics ('likes', 'comments', 're-tweets' and 'follows') are commonly used by industry and are said to be more granular than number of followers (Lee, Hosanagar, & Nair, 2018). The metrics are also measurable actions that consumers take on social media and emphasise the co-creative nature of the medium (Barger et al, 2016;Tafesse, 2016).…”
Section: Consumer Engagementmentioning
confidence: 99%
“…The effectiveness of such approaches is underpinned by research that found humorous, brand "personality" advertising in Facebook to be more effective than informative content 46 and research with children that found that humour was the most liked advertising tactic 47 . Similarly, Australian Facebook pages, some of which were among the most popular with 13-17 year olds, employed marketing techniques, often unique to social media, that could increase consumer interaction and engagement and even facilitate direct product purchase 40 .…”
Section: The Power Of Digital Marketingmentioning
confidence: 99%
“…El objetivo de gestión del marketing digital consiste en hallar las formas más eficaces para lograr el engagement de los usuarios objetivo, y así lograr en ellos los efectos deseados. En términos generales, las publicaciones informativas de las marcas provocan menos engagement que aquellos que se refieren a la personalidad de cada marca, con recursos humorísticos o emocionales (Lee, Hosanagar y Nair, 2015). Esta misma lógica proveniente del marketing digital, que busca involucrar a los usuarios para incrementar la difusión de las publicaciones y el sentimiento positivo, es utilizada además tanto por agencias de gobierno (Bhattacharya, Srinivasan y Polgreen, 2017) como por organizaciones sin fines de lucro (Syrdal y Briggs, 2016).…”
Section: Emergencia Del "Conversacionalismo"unclassified